Improved direct measurement of the parity-violation parameter Ab using a mass tag and momentum-weighted track charge - Abe, K; Abe, K; Abe, T; Adam, I; Akimoto, H; Aston, D; Baird, K; Baltay, C; Band, H; Barklow, T; Bauer, J; Bellodi, G; et al. (2003)
The highly polarized SLC electron beam and precise vertexing capabilities of the SLD detector were exploited to perform a direct measurement of Ab=0.906±0.022(stat)±0.023(syst), from the 1996-1998 SLD data sample. Combined with previously published result based on the 1993-1995 data sample, Ab=0.907 ± 0.020(stat) ±0.024(syst) was found for the full 1993-1998 data sample.